069 Progressive multifocal leukoencephalopathy in good's syndrome. Issue 12 (14th November 2019) - Edwards, M; Cousins, R; Smith, R; Hinds, NP
Abstract : A 65-year-old retired paramedic presented with progressive visual disturbance, cognitive impairment and behavioural change over a course of 3 months. At the time of admission he was cortically blind and disoriented to time, place and person. His past medical history included a recently resected thymoma. An MRI Head with contrast revealed bilateral white matter signal change mainly in occipital lobes extending to both temporal and parietal lobes. This was non-enhancing with no obvious oedema. His basic CSF parameters were normal and JCV antibodies werenegative. However his CSF JCV PCR was significantly high and consistent with a diagnosis of progressive multifocal leukoencephalopathy (PML). HIV testing was negative and he was not taking any immunosuppressive therapy. The patient was found to be hypogammaglobulinaemic as well having a low B-cell count. In the context of a thymoma this was a case of Good's syndrome. Unfortunately the patient deteriorated further due to a hospital acquired pneumonia and he was palliated prior to his death. PML is a rare diagnosis and most often related to HIV or immunosuppression. It has been reported in cases of hypogammaglobulinaemia but this is thought to be one of only a handful of cases of PML in Good's syndrome.